The Gastrointestinal Aspects of Halitosis. (2010) - Kinberg, Sivan; Stein, Miki; Zion, Nataly; Shaoul, Ron
Abstract : BACKGROUND: Halitosis is a common human condition for which the exact pathophysiological mechanism is unclear. It has been attributed mainly to oral pathologies. Halitosis resulting from gastrointestinal disorders is considered to be extremely rare. However, halitosis has often been reported among the symptoms related to Helicobacter pylori infection and gastroesophageal reflux disease. OBJECTIVE: To retrospectively review the experience with children and young adults presenting with halitosis to a pediatric gastroenterology clinic. METHODS: A retrospective chart review of patients diagnosed with halitosis as a primary or secondary symptom was conducted. All endoscopies were performed by the same endoscopist. RESULTS: A total of 94 patients had halitosis, and of the 56 patients (59.6%) who were recently examined by a dental surgeon, pathology (eg, cavities) was found in only one (1.8%). Pathology was found in only six of 27 patients (28.7%) who were assessed by an otolaryngology surgeon. Gastrointestinal pathology was found to be very common, with halitosis present in 54 of the 94 (57.4%) patients. The pathology was noted regardless of dental or otolaryngological findings. Most pathologies, both macroscopically and microscopically, were noted in the stomach (60% non- H pylori related), followed by the duodenum and the esophagus. Fifty-two of 90 patients (57.8%) were offered a treatment based on their endoscopic findings. Of the 74 patients for whom halitosis improvement data were available, some improvement was noted in 24 patients (32.4%) and complete improvement was noted in 41 patients (55.4%). CONCLUSIONS: Gastrointestinal pathology was very common in patients with halitosis regardless of dental or otolaryngological findings, and most patients improved with treatment.